Programm „Aufnahmedorf”: Soziale Reintegration von obdachlosen Familien in dörflicher Umgebung (Anfangserfahrungen in Tarnabod 2004-2006) - Büki, Péter; Vecsei, Miklós; Kohányi, Miklós (European Journal of Mental Health, 2006)
‘Host Village’ Program: Societal Reintegration of Homeless Families in Rural Environments (Initial Experience in the Village of Tarnabod, 2004–2006): The paper presents an alternative method of social care, still in the phase of model experiment. The method is effective both for homeless families or those threatened by housing problems, and for the reviving of deprived rural settlements. This model experiment is twofold in nature: it may alleviate the homelessness problem on the one hand, and contribute to community social work on the other. The paper briefly outlines the background and the evolvement of the model experiment as embedded in the history of the homelessness problem in Hungary in the period after the collapse of communism (since 1990). As a ‘social diagnosis’, the ‘Host Village’, that is, Tarnabod in Heves County, and its inhabitants are presented. Then the main milestones of our practical work are reported from the village bus, through the launch of household farming, to the opening of a manufacturing plant in the village. Finally, we mention our plans for the future. In sum, the main pillars of the Host Village Model Experiment are social work, settlement development, employment policy, and, to some extent, rural development and agriculture as a result of the cooperation of several civil organisations and a local village government.